Knowledge and practice regarding prevention of occupational hazards among traffic policemen in Kathmandu - Panta, S; Neupane, M (Journal of Chitwan Medical College, 2017)
Occupational health hazards are hazards of exposure to pollution, noise and vibrations in the working environment (ILO). This study aim to find out the knowledge and practice on prevention of occupational health hazards among traffic policemen in Kathmandu valley. A descriptive study employing probability sampling was used to select 282 traffic policemen who were employed in the traffic police stations of Kathmandu. Where Self administered questionnaire was used to collect the data. Data were analyzed by using SPSS such as frequency, percentage, mean and standard deviation and chi-square test. Findings depicted that less than half of respondents (40.4%) had fair knowledge on prevention of occupational health hazards. The highest mean percentage score was in the area of effects and prevention of dust or gas about 70%. The level of knowledge was found significant association with age (p=0.029), government provided by safety measures (p=0.021). More than half (54.6%) of respondents had poor preventive practices, such as wearing gloves, back support belts, compression stocking, apply sunscreen cream and wearing ear plug on duty hour. The level of practice was found to have significant association with age group of respondents (p=0.038), sex (p=0.009) and work experience (p=0.048). It is concluded that traffic policemen knowledge regarding prevention of occupational health hazards had fair knowledge but poor preventive practices. This study reveals the need for awareness program for prevention of occupational health hazards among traffic policemen